خطر السرقة العلمية وآليات معالجتها - جديد عبد الكريم; عيشوش نعيمة (University Of Eloued جامعة الوادي, 2023)
In recent years, many phenomena related to scientific research have emerged, including scientific theft, i.e. plagiarism on the intellectual property of others. It is considered one of the negative phenomena that research institutions, especially university ones and scientific research centers suffer from. The community, where the aim of this study was the commitment of researchers to scientific honesty when transferring from these works by attributing the information to its original author and creator as the owner of the moral right over it, otherwise the researcher bears the responsibility for that, and spreading the culture of scientific and academic integrity among researchers while drawing their attention to the penalties imposed on them in The case of scientific theft, which has worsened in light of the knowledge and information explosion that we are currently witnessing, and the enactment of laws for that, as we used in this study the descriptive analytical approach، The most prominent result of the study is an immoral act based on stealing the efforts of other researchers, and the need to work to increase intellectual production while working on providing training courses for the advancement and development of academic writing while highlighting the importance of scientific integrity in the advancement of intellectual production. The ease of using the Internet plays in the readiness of research. Scientific presentation highlighting the role played by the university in addressing scientific plagiarism and raising awareness among students.
The danger of scientific plagiarism and mechanisms to address it
مداخلة
Keywords: السرقة العلمية; البحث العلمي; الإنتاج الفكري; الأمانة العلمية; Scientific theft; Scientific Research; Intellectual production; Scientific Secretariat